EVALUASI PEMBELAJARAN TEMATIK DALAM MEMBENTUK PROFIL PELAJAR PANCASILA PADA MADRASAH IBTIDAIYAH DI KABUPATEN SINTANG - Kusgiyanti, Ety; Wicaksono, Luhur; Rajati, Tati (STKIP Persada Khatulistiwa Sintang, 2024)
The aim of this study is to describe thematic learning in forming the Pancasila Student Profile by knowing the planning, implementation and knowing the learning assessment tools in forming the Pancasila Student Profile. This study uses an illuminative evaluation model, with data sources coming from four Elementary Madrasah in Sintang Regency. The data were qualitative data collected through observation, interview, and documentation techniques. Triangulation of techniques and sources is used to ensure the validity of the data. The results of the analysis of learning carried out at class IV in four (4) Elementary Madrasah in Sintang Regency in forming the Pancasila Student Profile found 1) Each Madrasah has a learning planning formulation consisting of a syllabus document and a Learning Implementation Plan. The syllabus document adopts the formulation issued by the Education and Culture Office or downloaded via the internet; 2) The learning implementation process at Madrasah Ibtidaiyah in Sintang Regency is carried out based on the characteristics of each Madrasah while still adhering to the syllabus. Some Madrasah use Dhuha prayer as an opening activity, some use Tahfidz activities as routine activities in the morning. The implementation of the three stages in learning in general is carried out well; 3). The critical reasoning aspect according to Bloom's taxonomy theory has not been reflected in the learning assessment tools which are prepared or used by teachers.